The Safety Standards Protecting Against the COVID-19 Disease in Communal Cultural Institutions in Poland as Exemplified by Selected Communes - Bohdan, Anna; Maziarz, Bartosz; Dornfeld-Kmak, Agnieszka (Journal of Public Governance, 2022)
Objectives: The article aims to present the principles of conducting activities by communal cultural institutions in Poland in the era of the pandemic in the context of actions taken to reduce the risk of virus transmission between unit employees and between the unit employees and people using its services.Research Design & Methods: The article uses dogmatic-legal analysis and the document analysis metod.Findings: The employed methodology enabled the authors to establish that in communal cultural institutions in Poland measures were taken to respond to the COVID-19 pandemic in the context of the spread of the virus.Implications/Recommendations: According to the authors, the exposure of the measures against preventing the spread of the virus in communal cultural institutions can deepen cooperation between these units in implement- ing effective measures to counteract the spread of the virus.Contribution/Value Added: In the face of the COVID-19 pandemic and the dynamically changing health situation in the world, as well as the related lack of up-to-date sources and studies, partial scientific studies demonstrating a selected fragment of reality are critical. In the short and long term, they will enable researchers to learn about the type of actions taken by communal cultural institutions in terms of preventing the spread of the virus.Keywords: COVID-19 pandemic, communal cultural institutions, safety procedures during the COVID-19 pandemic, public policies.Article classification: research paperJEL: H12, H56, H83